Common Fixed-Point Problem for a Family Multivalued Mapping in Banach Space - Zhanfei Zuo (International Journal of Mathematics and Mathematical Sciences)
It is our purpose in this paper to prove two convergents of viscosity approximation scheme to a common fixed point of a family of multivalued nonexpansive mappings in Banach spaces. Moreover, it is the unique solution in 𝐹 to a certain variational inequality, where 𝐹∶=∩∞𝑛=0𝐹(𝑇𝑛) stands for the common fixed-point set of the family of multivalued nonexpansive mapping 𝑇𝑛.